The Effect of Product Quality, Service Quality, and Trust on Purchasing Decisions for Brother Fish Farm Fish Product - Dian, Alvy; Rachmawati, Erny; Alfalisyado; Yusnar Kharismasyah, Alfato (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aimed to identify the effect of product quality, service quality, and trust on purchasing Brother Fish Farm fish product. This research uses quantitative methods and types of primary data. The population were consumers of Brother Fish Farm fish products, with 107 samples obtained using purposive sampling techniques-test data analysis using the Smart PLS calculation tool. The analysis results show that product quality has a significantly positive effect on purchasing decisions, service quality has a significantly positive effect on buying decisions, and trust has a significantly positive effect on purchasing decisions.